Flipped Classroom Model untuk Meningkatkan Kompetensi Guru dalam Menulis Karya Sastra Anak di Madrasah se-Kecamatan Playen - Sri Rahmiyati (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This best practice writing aims to describe the application of The Flipped Classroom Model as an effort to improve the competence of madrasah teachers in Playen District in writing children's literature as an effort to support literacy and the provision of learning media. The subjects of writing are 12 madrasah teachers in Playen District for the 2021/2022 academic year. Best practice writing uses descriptive qualitative methods. Collection of information on the results of writing using assessment instruments on literary documents made by teachers. The strategies or steps used in the flipped classroom models are (1) pre-classes are implemented for online material delivery and assignments; (2) in-class face-to-face activities are carried out in groups or individually to discuss and evaluate products; (3) after-class, carried out for editing, evaluation of activities and documentation. The results of the implementation of the flipped classroom model can improve teacher competence in, (1) writing poetry based on obtaining pre-class scores of 30.7% (less), in-class 57.9% (sufficient), after-class 81% (very good); (2) writing children's stories based on pre-class scores of 31% (less), in-class 57.8% (sufficient), after-class 80% (good); (3) Personally teachers have the confidence to write a literary work, participate in authorship events and create learning media from this writing skill.